EFEKTIVITAS DAUN GAMBIR ( UNCARIA GAMBIR ROXB ) UNTUK MENURUNKAN HALITOSIS YANG DISEBABKAN OLEH PLAK Studi di Panti Asuhan dan Pondok Pesantren Zuhriyah, Sleman, Yogyakarta - Irfan Irfan; Yayun Siti Rochmah; Moh Yusuf; Grahita Aditya (Faculty of Dentistry, Universitas Islam Sultan Agung, 2015)
Introduction: Halitosis is the smell of bad breath that comes out of the mouth. Gambir contained catechins which is a material that helps in inhibited bacteria and VSC (Volatic Sulfur Compound) as the cause of halitosis.Purpose: The aim of research to assess the effectiveness of gambir leaves against halitosis is caused by plaque.Methods: The method in this research is pre experimental research with 18 research subjects students. Halitosis parameter measurements made before and after the use of gambir for 3 days. VSC gas is measured using the tool